PHYTOCHEMICAL AND PHARMACOLOGICAL EVALUATION OF CALLISTEMON CITRINUS FOR ANTIDEPRESSANT ACTIVITY IN ALBINO MICE - Pendyala, Vijetha; Thaakur, Santhrani (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study was carried out to find out the antidepressant activity of different fractions of stems and leaves of Callistemon citrinus(CC). The efficacy of the fractions was compared with the standard reference drug imipramine. Methods: All the studies were conducted according to the ethical guidelines of CPCSEA. Healthy adult albino mice weighing 20-30 g were used asexperimental animals. The leaves of CC were extracted with alcohol and fractionated with chloroform and petroleum ether. All the fractions weresubjected for preliminary phytochemical screening, using various qualitative tests. In the present investigation, tail suspension test (TST) and forcedswim test (FST) are selected as animal models for evaluation of antidepressant activity in albino mice. Results: The preliminary phytochemical screening of CC has revealed the presence of carbohydrates, tannins, and flavonoids in a hydroalcoholicfraction. Chloroform fraction showed positive results toward flavonoids, alkaloids, tannins, glycosides, and steroids. Alcoholic and chloroform extract(100 and 200 mg/kg p.o.) of CC administered orally for 14 successive days had decreased the immobility periods significantly in a dose-dependentmanner in both TST and FST, showing significant antidepressant-like activity. The activities of the extracts were found to be comparable to imipraminein both FST and TST. Conclusions: Although a number of synthetic drugs are being used as a standard treatment for clinically depressed patient, they have adverseeffects that can compromise the therapeutic treatment. In the traditional systems of medicine, many plants and formulations have been used to treatdepression for thousands of years. The results of the study indicate that CC can be used as an antidepressant herb.